RESULTS OF DETERMINING THE KINETICS OF MOISTURE CONTENT AND TEMPERATURE IN MEAT DURING CONDUCTIVE DRYING UNDER CONDITIONS OF COMPRESSION TO THE CRITICAL POINT OF MOISTURE CONTENT - PONOMARENKO, BOGDAN; SKRYPNYK, VIACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Dried products are in high demand due to their preserved nutritional properties, extended shelf life, and ease of transportation. However, the drying process for food materials often involves high energy consumption. Reducing these costs is a pressing issue given the current energy situation in Ukraine. Conductive drying is one of the available methods that can lower energy consumption, but it remains insufficiently studied. In particular, the drying of meat using this method with double-sided heat application under compression opens new opportunities for a range of studies aimed at reducing energy consumption and shortening the process duration. This article presents the results of experiments on drying meat of various thicknesses (0.003 m, 0.005 m, and 0.007 m) using conductive drying with compression by heating surfaces under loads of 10 kg, 20 kg, and 30 kg during the first drying period, which lasted until the critical moisture content Wcr. The authors developed an analytical model for this process and analyzed the actual moisture content and temperature kinetics, which demonstrated dynamics similar to other drying methods throughout the process. The data indicate that the kinetics obtained under compression were shorter in duration. It was determined that further compression drying after reaching the critical moisture point Wcr is impractical since residual moisture is removed significantly more slowly under such conditions. Therefore, compression during the second drying period only prolongs the process and increases energy consumption. The experimental results showed that the best process performance was achieved with a sample thickness of δ=0.003 m and a compression load of G=30 kg.